Online Order Delivery On Customer Satisfaction - Siti Maemunah; Laurentius Bagus Permana; Yuliantini Yuliantini; Mudjiarjo Mudjiarjo; Sri Rahardjo (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2023)
The research aims to overcome the gap between expectations and the reality of the service perceived by online delivery order customers, operational performance and service quality on customer satisfaction at shipping companies. The research sample is 120 customer respondents from import shipping companies in Jakarta. Data collection techniques using a questionnaire. The data analysis method used is path analysis. The results of online order delivery research adopting e-service and the web have succeeded in influencing service quality. E-service improves service quality, meaning that it has an effect on improving service quality on customer satisfaction. Service quality is able to function as a mediator to deliver online orders to customer satisfaction. Online order delivery is implemented to increase customer satisfaction so that service quality as an intervening variable is proven to function to strengthen the effect of online delivery orders on customer satisfaction. Service quality is able to function as a mediator or mediate the indirect effect of operational performance on customer satisfaction.